Pharmacokinetics of Colistin in the Gastrointestinal Tract of Poultry Following Dosing via Drinking Water and Its Bactericidal Impact on Enteric Escherichia coli - Mead, Andrew; Richez, Pascal; Azzariti, Stefano; Pelligand, Ludovic (Frontiers in Veterinary Science, 2021)
Colistin, a last line antibiotic of major importance in veterinary medicine and critical importance in 10 human medicine, is authorized to treat gastrointestinal (enteric) infections caused by non-invasive E. 11 coli in multiple veterinary species including poultry. Its use in veterinary medicine has been implicated 12 in the widespread prevalence of mobilized colistin resistance. 13 The objectives of this study were to determine the intestinal content reached in broiler chickens during 14 72 h treatment with colistin, evaluate the associated impact on intestinal E. coli density, and selection 15 of less susceptible E. coli populations. In this study, 94 broiler chickens were administered a dose of 16 75 000 IU/kg/day via drinking water. Intestinal samples were collected pre-, during- and post-dosing. 17 Luminal intestinal content was assessed for colistin content by UHPLC-MS/MS, E. coli were isolated 18 and enumerated on UriSelect agar™. Minimum inhibitory concentration (for 8 isolates per intestine 19 per animal) was determined and when higher than the Epidemiological Cut-off (ECOFF 2 mg/L), 20 isolates were screened for mcr-1 to 5. 21 Colistin content increased during treatment to a maximum of 5.09 mg/kg. During this time the total 22 population of E. coli showed an almost 1000-fold reduction. An apparent increase in the relative 23 abundance of E. coli with an MIC≥ECOFF, either mcr-negative (6.25 – 10.94%) or mcr-1-positive 24 (4.16 – 31.25%) was observed, although this susceptibility shift was not maintained post-treatment. 25 Indeed, following cessation of dosing, colistin was eliminated from the intestine and content was below 26 LOQ (1.1 mg/kg) within 4 hours and median MIC of E. coli isolates returned below baseline thereafter. 27 Few isolates with a lower susceptibility (mcr-1-positive or negative), were however observed at the 28 end of the study period indicating maintained sub-populations in the chicken gut. The results of this 29 study show limited impact on long-term maintenance of less susceptible E. coli populations as a direct 30 result of colistin treatment in individual birds.